Pengaruh Return on Equity dan Current Ratio terhadap Return Saham pada Perusahaan Manufaktur Subsektor Otomotif dan Komponen yang Terdaftar di Bursa Efek Indonesia - Jaja Muhammad Zakaria; Nasution Nasution; Estalita Julia (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2022)
This research was conducted on automotive subsector Manufacturing companies and components listed on Indonesia Stock exchange for the period 2012-2017. The phenomenon that occurs in recent years is that the stock returns that investors receive fluctuate according to the change in the stock price and the decision to provide dividends. So that investors will suffer losses when the stock price drops. The methods used in this study are quantitative methods. This study uses multiple linear regression analysis methods. The data used is the secondary data sourced from the annual financial subsector Manufacturing Company and components listed on the Indonesia Stock exchange for the period of 2012-2017. The results showed that return On Equity does not partially affect return on shares. Return on equity has significance value. The current ratio does not partially affect the return of the stock. According to R2 count shows that the variables researched are Return On Equity and Current Ratio which affect 6.4% of the sale.